A comunicação intersistêmica entre direito e saúde como condição de regulação e eficácia de direito fundamental, nas decisões da OMS, OPAS, SUS, ANVISA e STF durante a emergência da COVID-19 no Brasil - Oliveira, Bianca Neves de (2023)
The objective of this dissertation is to analyze the intersystemic communicational semantics generated by relations between the health system and the legal system, through decisions made by organizations, notably, from the STF, facilitated by standards from WHO, PAHO, SUS, ANVISA, with the aim of contribute to regulating the impact of COVID-19 in Brazil. The choice of this theme is necessary due to to the pandemic dimension that affected the lives of the entire population, generating unrest and immense crisis social. The methodology adopted is Systemic Pragmatics, linked to the theory of social systems, mainly, in the perspective of Niklas Luhmann, revised by Gunther Teubner, based on analysis communication. Likewise, it is part of the Fundamental Rights discourse theory. The technique of research used is bibliographical research, mainly in books, articles, laws, analysis of STF jurisprudence, international treaties and conventions. The argument was divided into three chapters. The research demonstrates that there is a structural coupling between the system of law and the system of health, which made it possible to regulate the developments of COVID-19. The impact of this pandemic, although immense and dramatic, it was controlled thanks to this systemic dimension. The fundamental right to health was the great standard of these fights.